Homeless in Kuala Lumpur: a way out of the street - Hamdan, Nur Syuhadah; Herman, Siti Sarah (Malaysian Institute of Architects, 2020)
The number of homeless in Kuala Lumpur has increased ten-fold over the past few years. Over the years, awareness about the welfare of the street peoples has been on the rise. Although the intention of the groups is good, the overflow of this charity movement proved to create another issue, over-giving. The lack of effective intervention from the government agencies also has been blamed for worsening the issue further. Hence, the paper intends to come out with a long term programme that aids the homeless of Kuala Lumpur beyond the basic need and to be independent and out of the street. To archive, the aim is by identifying a set of objectives which are: to categorise the homeless into several groups, to analyse the current policies and initiative programmes in Malaysia, and lastly to compare the existing strategies and aids for the homeless in Malaysia with others countries. A qualitative content analysis method is used in this study by summarizing literature review on the programmes that aid the homeless to come out of homelessness in Malaysia and other countries. Comparison is focusing on government intervention programmes as well as national policies regarding the homeless issue. This paper will hopefully bring significant changes to the way we design and execute homeless intervention programmes in the future.